Behavioral and electrophysiological evidence for a dissociation between working memory capacity and feature-based attention. (August 2020) - Harris, Anthony M.; Jacoby, Oscar; Remington, Roger W.; Becker, Stefanie I.; Mattingley, Jason B.
Abstract: When attending to visual objects with particular features, neural processing is typically biased toward those features. Previous work has suggested that maintaining such feature-based attentional sets may involve the same neural resources as visual working memory. If so, the extent to which feature-based attention influences stimulus processing should be related to individuals' working memory capacity. Here we used electroencephalography (EEG) to record brain activity in 60 human observers while they monitored stimulus streams for targets of a specific color. Distractors presented at irrelevant locations evoked strong electrophysiological markers of attentional signal enhancement (the N2pc and PD components) despite producing little or no behavioral interference. Critically, there was no relationship between individual differences in the magnitude of these feature-based biases on distractor processing and individual differences in working memory capacity as measured using three separate working memory tasks. Bayes factor analyses indicated substantial evidence in support of the null hypothesis of no relationship between working memory capacity and the effects of feature-based attention on distractor processing. We consider three potential explanations for these findings. One is that working memory and feature-based attention draw upon distinct neural resources, contrary to previous claims. A second is that working memory is only related to feature-based attention when the attentional template has recently changed. A third is that feature-based attention tasks of the kind employed in the current study recruit just one of several subcomponents of working memory, and so are not invariably correlated with an individual's overall working memory capacity.